DIGITAL TRANSFORMATION IN INDUSTRIAL ENTERPRISES IMPORTANCE AND PROSPECTS - Ruhshona To’ychiyeva Arslonbek qizi (Ecominds Press, 2025)
This article discusses the application of digital transformation in industrial enterprises, the main issues in organizing digital transformation processes in enterprises. The purpose of this study is to identify the main problems and opportunities in organizing digital transformation processes in industry based on statistical analysis methods. The main problems of digital transformation were analyzed, a number of problems and obstacles to digital transformation were studied. The article also presents opinions on foreign experiences of the digital transformation process, its role in the economy, advantages and disadvantages, and solutions.
Keywords: Digital transformation, digital economy, digital technologies, internet, innovation, process digitization, industrial enterprises, digitization, business models, digital business model, ecosystem, digital transformation ecosystem, digital innovations.